Analisis Konten Husein Basyaiban Terhadap Pemboikotan Produk-Produk yang Mendukung Israel melalui Media TikTok - Nasution, Nalla Shakira; Khatibah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This research aims to determine Husein Basyaiban content analysis regarding the boycott of products that support Israel via TikTok media. This research uses a qualitative descriptive method with a content analysis approach. The results of this research show that boycotting products that support Israel is not absolutely mandatory. Still, it is better to replace them with other products that do not support Israel if possible. However, if the product is still more suitable or cannot be replaced, users can continue using it. It is important to ensure the correctness of the information before deciding to boycott a product, according to the teachings in Surah Al-Hujurat verse 6. A positive view of Husein Basyaiban's content shows that the content educates users to choose products more wisely and not be influenced by inaccurate news. This boycott is also seen as a humanitarian act carried out not only by Muslims but also by non-Muslims